2014
DOI: 10.2147/jbm.s55769
|View full text |Cite
|
Sign up to set email alerts
|

Toward a patient-based paradigm for blood transfusion

Abstract: The current “manufacturing paradigm” of transfusion practice has detached transfusion from the clinical environment. As an example, fresh whole blood in large-volume hemorrhage may be superior to whole blood reconstituted from multiple components. Multicomponent apheresis can overcome logistical difficulties in matching patient needs with fresh component availability and can deliver the benefits of fresh whole blood. Because of the different transfusion needs of patients in emerging economies and the vulnerabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…For example, in Kenya at the Kijabe Hospital, group O, nonleukoreduced CWB, stored at 4°C for up to 35 days, is commonly provided to patients (J. Kibuchi and S. Letchford, oral communication, August 15, 2015). The use of WB in developing nations has historically been limited primarily due to the lack of systems or capacity to produce components; however, some areas have resisted the adoption of component therapy for multiple other reasons …”
Section: Wb Availabilitymentioning
confidence: 99%
“…For example, in Kenya at the Kijabe Hospital, group O, nonleukoreduced CWB, stored at 4°C for up to 35 days, is commonly provided to patients (J. Kibuchi and S. Letchford, oral communication, August 15, 2015). The use of WB in developing nations has historically been limited primarily due to the lack of systems or capacity to produce components; however, some areas have resisted the adoption of component therapy for multiple other reasons …”
Section: Wb Availabilitymentioning
confidence: 99%
“…The primary blood product that is currently the safest and has the least side effects is WFWB. 28 , 39 41 If complete component therapy is not available or does not adequately correct coagulopathy in patients with life-threatening hemorrhage at risk for massive transfusion, the risk–benefit ratio favors the use of WFWB transfusion. In addition, recent evidence suggests that WFWB is potentially more efficacious than stored component therapy.…”
Section: Warm Fresh Whole-blood (Wfwb) Transfusionmentioning
confidence: 99%
“…Treatment of combat-wounded victims at the 31st Combat Support Hospital (31st CSH) in Baghdad between 2004–2005 revealed that there were some advantages to using fresh whole blood at 20-24°C; military doctors proposed that whole blood should be used under extreme conditions with low temperatures. Farrugia et al [ 25 ] propose that in large-volume hemorrhage, fresh whole blood in may be superior to whole blood that has been reconstituted from multiple individual components. Nevertheless, research conducted by the United States Army revealed that between March 2003 and July 2007, over 6,000 units of warm fresh whole blood were used for transfusion in field hospitals of Afghanistan and Iraq.…”
Section: The Treatment Of Hypothermia In Cold Environmentsmentioning
confidence: 99%